Komitmen Organisasi, Risiko Kerja Dan Dampaknya Terhadap Loyalitas Pegawai Pengurus Koperasi Tuah Selebar Daun Kecamatan Muara Telang Kabupaten Banyuasin - Nida Wahyu Audes Mantya; Mohammad Kurniawan; Yeni Yeni (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2026)
This study aims to analyze the effect of organizational commitment and work risk on administrators loyalty at Tuah Selebar Daun Cooperative, Muara Telang District, Banyuasin Regency. This research employs a quantitative approach using a survey method. Data were collected through questionnaires distributed to 112 respondents consisting of cooperative administrators. The data analysis techniques used include validity testing, reliability testing, classical assumption testing, and multiple linear regression analysis using SPSS. The results show that organizational commitment has a positive and significant effect on administrators loyalty, with a t-value of 2.000 and a significance value of 0.048 < 0.05. Furthermore, work risk also has a positive and significant effect on administrators loyalty, as indicated by a t-value of 3.402 and a significance value of 0.001 < 0.05. Simultaneously, the F-test results indicate that organizational commitment and work risk have a significant effect on administrators loyalty, with an F-value of 31.292 and a significance value of 0.000 < 0.05. The coefficient of determination (R²) of 0.365 indicates that administrators loyalty is influenced by 36.5% by organizational commitment and work risk, while the remaining 63.5% is influenced by other variables not examined in this study. Based on these findings, it can be concluded that increasing administrators loyalty can be achieved through strengthening organizational commitment and implementing effective and sustainable work risk management. The results of this study are expected to provide useful input for cooperative management in developing human resource management policies to enhance administrators loyalty.